2021
DOI: 10.1038/s42254-020-00267-1
|View full text |Cite
|
Sign up to set email alerts
|

Physics of viral dynamics

Abstract: Protein shells that surround the viral genome. Triangulation numbers Classification system, developed by Caspar and Klug, for icosahedral viruses. T-numbers are integers and contain information on the number of protein subunits that make up a capsid. Virions Viral particles, composed of both capsid proteins and the viral genome, that can successfully infect cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 200 publications
4
58
0
2
Order By: Relevance
“…The first type depends on a specific RNA structure and involves the TLS located at the 3 end of BMV genomic RNAs [14]. It was shown that the encapsidation of BMV RNA lacking TLSs is not effective but can be restored after complementation with yeast tRNA or separate TLSs [8]. We show that yeast tRNA alone is sufficient to mediate the formation of stable and homogenous VLPs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The first type depends on a specific RNA structure and involves the TLS located at the 3 end of BMV genomic RNAs [14]. It was shown that the encapsidation of BMV RNA lacking TLSs is not effective but can be restored after complementation with yeast tRNA or separate TLSs [8]. We show that yeast tRNA alone is sufficient to mediate the formation of stable and homogenous VLPs.…”
Section: Discussionmentioning
confidence: 93%
“…Capsid assembly is currently being extensively analyzed, and some general rules of this process have already been determined. The formation of capsid depends on the temperature, pH, ionic strength, CP concentration and features of the encapsidated core molecules [6][7][8]. Due to the recent development of experimental and computational techniques in the field of physical virology, the static descriptions of viral particles have been replaced by dynamic models based on soft-mode dynamics and kinetic trapping [9].…”
Section: Introductionmentioning
confidence: 99%
“…To answer the question of whether viruses are alive or not, I base my argument in support of considering viruses as living entities obviously on my own definition of life (this paper), as well as on what we know about the biology of viruses. First, viruses, like all cellular entities in nature, are composed of organic molecules; a virus consists of a nucleic acid (DNA or RNA), which is its genetic material as in all living things, and a protein capsid encoded by the viral genome that protects the viral genetic material and participates in the propagation of the virus in the host; viral capsids show fascinating dynamics during the viral life cycle [ 49 ]. Secondly, viruses are highly organized structures.…”
Section: Are Viruses Alive?mentioning
confidence: 99%
“…In recent decades, natural spherical viral capsids have attracted considerable attention for application as nanoreactors, vaccine platforms, and nanocarriers for drug delivery systems [ 9 , 10 , 11 , 12 ]. Physicochemical analysis of the self-assembly processes of viral capsids is an important aspect in molecular biology and valuable for the molecular design of viral capsids as functional materials [ 13 , 14 ]. To elucidate the self-assembling process of natural viral capsids, intermediate structures have been previously detected by ion mobility separation-mass spectrometry, interferometric scattering microscopy, transmission electron microscopy (TEM), and atomic force microscopy (AFM) under dilute conditions [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical analysis of the self-assembly processes of viral capsids is an important aspect in molecular biology and valuable for the molecular design of viral capsids as functional materials [ 13 , 14 ]. To elucidate the self-assembling process of natural viral capsids, intermediate structures have been previously detected by ion mobility separation-mass spectrometry, interferometric scattering microscopy, transmission electron microscopy (TEM), and atomic force microscopy (AFM) under dilute conditions [ 14 , 15 , 16 ]. Nonetheless, the formation of viral capsids by self-assembly actually occurs in molecular crowding environments, such as a host cell [ 17 ].…”
Section: Introductionmentioning
confidence: 99%